Addition to the knowledge of Xylaria (Xylariaceae, Ascomycota) in Santa Catarina, Southern Brazil - Trierveiler Pereira, Larissa (2009)
Xylaria specimens have been collected in the State of Santa Catarina, Southern Brazil, since the 19th century, primarily by European naturalists such as Ernst Ule and Alfred Möller. Few comprehensive surveys or Xylaria collections have been made by Brazilians in the State until recently. New knowledge has been gained from the authors' recent survey and examination of specimens from the Florianópolis metropolitan area. Among the species discussed are a new species, Xylaria nigromedullosa, and eleven other species, including X. adscendens, X. allantoidea, X. anisopleura, X. comosa, X. cubensis, X. curta, X. ianthinovelutina, X. magnoliae var. microspora, X. mellissii, X. obovata, and X. telfairii. Most collections were obtained from dead wood, with a few found growing on fallen fruits. Seven species are new records from Santa Catarina and X. magnoliae is a new record for Brazil. Full descriptions, illustrations, and a key to the Xylaria collections now curated in FLOR are provided.